Daidzein alleviates high glucose-induced pyroptosis of renal tubular epithelial cells - CHEN Caiwei, WU Yueping, WANG Zhuansuo, LUO Qiang, XING Bozhen (Jichu yixue yu linchuang, 2023)
Objective To investigate the impact of daidzein (DAI) on the pyroptosis of renal tubular epithelial cells induced by high glucose by regulating NOD-like receptor protein 3 (NLRP3)/caspase-1 signal pathway. Methods HK-2 cells were divided into control group (NC group) (5.5 mmol/L D-glucose), HG group(30 mmol/L D-glucose), DAI-L, DAI-M, DAI-H groups (HK-2 cells were incubated with 30 mmol/L D-glucose and 25, 50, 100 μmol/L DAI,respectively), and DAI-H+LPS group (HK-2 cells were incubated with 30 mmol/L D-glucose, 100 μmol/L DAI and 1 μg/mL LPS). MTT assay was applied to detect the cytotoxicity and proliferation of HK-2 cells; the apoptosis of HK-2 cells was detected by flow cytometry. The level of interleukin-1β (IL-1β) and inter-leukin-18 (IL-18) in HK-2 cells was detected by ELISA. The morphology of pyroptosis cells was observed by scanning electron microscope. Immunofluorescence staining was applied to detect pyroptosis related proteins. The expression of NLRP3, cleaved casase-1 and GSDMD-N was detected by Western blot. Results In NC group, the cells were spherical with regular boundaries, while in HG group, the cells swelled and became larger with irregular boundaries; the OD value (490 nm) of HK-2 cells in HG group was obviously lower than that in NC group(P＜0.05), the apoptosis rate, IL-1β, IL-18 contents, NLRP3, cleaved casase-1, GSDMD-N protein level of HK-2 cells were obviously higher (P＜0.05); After DAI treatment, the swelling of cells was alleviated, the A value (490 nm) of HK-2 cells increased significantly (P＜0.05), the apoptosis rate of HK-2 cells, IL-1 β, IL-18 content, NLRP3, cleaved-caspase-1 and GSDMD-N protein levels were significantly decreased(P＜0.05) and the therapeutic effect of DAI was dose-dependent; LPS eliminated the beneficial effect of DAI-H on high glucose induced apoptosis of renal tubular epithelial cells. Conclusions DAI may alleviate pyroptosis of renal tubular epithelial cells induced by high glucose through inhibition of NLRP3/caspase-1 signaling pathway.